Wet scavenging of soluble gases in DC3 deep convective storms using WRF‐Chem simulations and aircraft observations. Issue 8 (21st April 2016) - Bela, Megan M.; Barth, Mary C.; Toon, Owen B.; Fried, Alan; Homeyer, Cameron R.; Morrison, Hugh; Cummings, Kristin A.; Li, Yunyao; Pickering, Kenneth E.; Allen, Dale J.; Yang, Qing; Wennberg, Paul O.; et al.
Abstract: We examine wet scavenging of soluble trace gases in storms observed during the Deep Convective Clouds and Chemistry (DC3) field campaign. We conduct high‐resolution simulations with the Weather Research and Forecasting model with Chemistry (WRF‐Chem) of a severe storm in Oklahoma. The model represents well the storm location, size, and structure as compared with Next Generation Weather Radar reflectivity, and simulated CO transport is consistent with aircraft observations. Scavenging efficiencies (SEs) between inflow and outflow of soluble species are calculated from aircraft measurements and model simulations. Using a simple wet scavenging scheme, we simulate the SE of each soluble species within the error bars of the observations. The simulated SEs of all species except nitric acid (HNO3 ) are highly sensitive to the values specified for the fractions retained in ice when cloud water freezes. To reproduce the observations, we must assume zero ice retention for formaldehyde (CH2 O) and hydrogen peroxide (H2 O2 ) and complete retention for methyl hydrogen peroxide (CH3 OOH) and sulfur dioxide (SO2 ), likely to compensate for the lack of aqueous chemistry in the model. We then compare scavenging efficiencies among storms that formed in Alabama and northeast Colorado and the Oklahoma storm. Significant differences in SEs are seen among storms and species. More scavenging of HNO3 and less removal of CH3 OOH are seen in storms with higher maximum flash rates, an indication of more graupel mass. Graupel is associated with mixed‐phase scavenging and lightning production of nitrogen oxides (NO x ), processes that may explain the observed differences in HNO3 and CH3 OOH scavenging. Key Points: Observed deep convective scavenging efficiencies simulated by simple scheme Simulated scavenging efficiencies highly sensitive to ice retention fraction Scavenging efficiencies vary among storms with different microphysics